Development of gelatin/carboxymethyl chitosan/nano-hydroxyapatite composite 3D macroporous scaffold for bone tissue engineering applications. (1st June 2018) - Maji, Somnath; Agarwal, Tarun; Das, Joyjyoti; Maiti, Tapas Kumar
Graphical abstract: Highlights: 3D macroporous scaffold was developed by high speed stirring and freeze drying method. SGC and NGC scaffolds had significantly different physico-chemical parameters. SGC scaffold were found more osteoconductive and osteoinductive than NGC scaffold. SGC scaffold showed greater penetration and higher viability of microtissues post-cryopreservation. Abstract: The present study delineates a relatively simpler approach for fabrication of a macroporous three-dimensional scaffold for bone tissue engineering. The novelty of the work is to obtain a scaffold with macroporosity (interconnected networks) through a combined approach of high stirring induced foaming of the gelatin/carboxymethyl chitosan (CMC)/nano-hydroxyapatite (nHAp) matrix followed by freeze drying. The fabricated macroporous (SGC) scaffold had a greater pore size, higher porosity, higher water retention capacity, slow and sustained enzymatic degradation rate along with higher compressive strength compared to that of non-macroporous (NGC, prepared by conventional freeze drying methodology) scaffold. The biological studies revealed the increased percentage of viability, proliferation, and differentiation as well as higher mineralization of differentiated human Wharton's jelly MSC microtissue (wjhMSC-MT) on SGC as compared to NGC scaffold. RT-PCR also showed enhanced expression level of collagen type I, osteocalcin and Runx2 when seeded on SGC. μCT and histological analysis further revealed a penetration of cellular spheroid to a greater depth in SGC scaffold than NGC scaffold. Furthermore, the effect of cryopreservation on microtissue survival on the three-dimensional construct revealed significant higher viability upon revival in macroporous SGC scaffolds. These results together suggest that high stirring based macroporous scaffolds could have a potential application in bone tissue engineering.